Dampak Program Pemberdayaan Masyarakat Desa terhadap Ketimpangan Wilayah Pedesaan dan Perkotaan: Penelitian - Devia Hetty Hernany; Khairullah Anshari; Amelia Puspita; Muhammad Haegel Rizfian; Nurul Syifa; Muhammad Rifqi Fadillah; Rosanda Nur Dwitara; Nur Ersanda (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study examines the extent to which the Village Community Empowerment Program (PPMD) impacts socio-economic inequality between rural and urban areas in Banjar Regency. Using a quantitative-qualitative approach, the study compares indicators of welfare, access to public services, economic participation, and social capital in villages receiving an empowerment intervention and their buffer urban areas. The analysis design involves Difference-in-Differences (DiD), propensity score matching (PSM), and social network analysis to capture direct, indirect, and spillover effects. The results are expected to provide policy evidence for the district government to design more equitable and effective empowerment interventions.